Interaction and electron transfer between ferredoxin-NADP(+) oxidoreductase and its partners: structural, functional, and physiological implications - Mulo P; Medina M (SPRINGER, 2022)
Ferredoxin-NADP(+) reductase (FNR) catalyzes the last step of linear electron transfer in photosynthetic light reactions. The FAD cofactor of FNR accepts two electrons from two independent reduced ferredoxin molecules (Fd) in two sequential steps, first producing neutral semiquinone and then the fully anionic reduced, or hydroquinone, form of the enzyme (FNRhq). FNRhq transfers then both electrons in a single hydride transfer step to NADP(+). We are presenting the recent progress in studies focusing on Fd:FNR interaction and subsequent electron transfer processes as well as on interaction of FNR with NADP(+)/H followed by hydride transfer, both from the structural and functional point of views. We also present the current knowledge about the physiological role(s) of various FNR isoforms present in the chloroplasts of higher plants and the functional impact of subchloroplastic location of FNR. Moreover, open questions and current challenges about the structure, function, and physiology of FNR are discussed.